ANALISIS SISTEM PENGHITUNGAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 21 ATAS GAJI PEGAWAI TETAP PADA KANTOR PELAYANAN PERBENDAHARAAN NEGARA KOLAKA UTARA. - Fadli, Zul; Wahditiya, Andi Andriani (Pusat Penerbitan dan Publikasi Ilmiah FEB-UMI, 2023)
Focus of this research examines how to calculate income tax article 21 on employee salaries. The aim of the research is to see the reality of the tax calculation and reporting system 21 on employee salaries. The research approach is descriptive quantitative with the data source, namely the tax calculation report article 21. The collection technique is carried out using observation, interviews and literacy studies. The analysis method is carried out using a descriptive approach or describing the factual reality of calculating tax article 21. The research results show that the income tax calculation system for article 21 is inadequate, because it still uses last year's PTKP